Consensus-based total-amount cooperative tracking control for multi-motor locomotive traction system. Issue 2 (January 2019) - Zhang, Changfan; Lin, Zhenzhen; Liu, Jianhua; He, Jing; Wu, Han; Li, Peng
Abstract: In locomotive traction system, unavoidable factors (such as idling and skidding) typically lead to the decline of traction performance of one or more motors, thereby resulting in the fluctuation of total torque traction amount. In this paper, the consensus-based total-amount cooperative tracking control (TACTC) is proposed to maintain the consensus of total torque traction amount with the given reference instruction. First, a disturbance observer is employed to estimate uncertain disturbances, then the output torque and observed values are fed back to design the total amount cooperative tracking control protocol, which is used to coordinate traction torque output redundancy of each individual motor. Simulation results show that the proposed approach is effective in reducing tracking time and tracking errors.